A Study in the Lexicographical Treatment of Arabic Synonyms - Heliel, Mohamed Helmy (Lexikos, 1997)
Abstract: Recently three dictionaries of Arabic synonyms were published with the aim of helping Arabic learners, writers and translators. Though Classical Arabic lexicography distinguishes itself in the field of synonymy, Modern Standard Arabic lacks reliable dictionaries in the field and hence the importance of analysing these three dictionaries, identifying their deficiencies and suggesting remedies to help establish a sound basis for a user-friendly dictionary of Arabic synonyms. This paper deals with certain lexicographical features closely related to synonymy, i.e. concerning corpus: selection of headwords and derivatives, arrangements of headwords, contextualization, collocations, figurative usage, equivalence, polysemy, register and style.